Immune and Smooth Muscle Cells Interactions in Atherosclerosis: How to Target a Breaking Bad Dialogue? - Ramel, Damien; Gayral, Stéphanie; Sarthou, Marie-Kerguelen; Augé, Nathalie; Nègre-Salvayre, Anne; Laffargue, Muriel (Frontiers in Pharmacology, 2019)
Inflammation is a well-known pathophysiological factor of atherosclerosis but its therapeutic targeting has long been ignored. However, recent advances in the understanding of the immune mechanisms implicated in atherosclerosis have unveiled several therapeutic targets currently undergoing clinical trials. These studies have also shed light on a dialogue between the immune compartment and vascular smooth muscle cells (VSMCs) that plays a critical role in atherosclerotic disease initiation, progression, and stabilization. Our review focuses on the link between cellular and soluble immune effectors and VSMC behavior at different phases of the pathology. Furthermore, we discuss the potential targeting of these interactions to efficiently prevent cardiovascular diseases.